2020
DOI: 10.5430/ijhe.v9n4p283
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Culture Formation of Future Social Workers in the Educational Process of Pedagogical University

Abstract: Article considers the essence of the process of communicative culture formation of future social workers in the educational process of the pedagogical university. The communicative culture is singled out and considered through an interdisciplinary approach in the professional education of social workers. The peculiarities of the communicative culture formation of future social workers in the educational process in the pedagogical university are highlighted. Emphasis is placed on the need to use various tools i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Spreadley's research also uses comparative analysis techniques, which reveal that the accelerated program at SD Muhammadiyah has advantages compared to traditional educational approaches. The results of the analysis showed that students who participated in the accelerated program achieved higher academic achievement and showed higher levels of satisfaction with their learning (Omelchenko et al, 2020). The program also successfully increases students' interest in learning and provides opportunities for them to interact with peers who have similar interests and intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…Spreadley's research also uses comparative analysis techniques, which reveal that the accelerated program at SD Muhammadiyah has advantages compared to traditional educational approaches. The results of the analysis showed that students who participated in the accelerated program achieved higher academic achievement and showed higher levels of satisfaction with their learning (Omelchenko et al, 2020). The program also successfully increases students' interest in learning and provides opportunities for them to interact with peers who have similar interests and intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…Maslow's Hierarchy of Needs, mentioned above, is an indicator of a person's set of needs, which always follow a sequence of steps. The higher the level of a need, or moving up a level of need, the fewer needs there are because other needs are considered met and fewer people reach that higher level [9].…”
Section: Introductionmentioning
confidence: 99%
“…Current issues of theory and practice of social work in Ukraine are considered by Bekh [4], Bekh and Bekh [5], Dubych [10], Kropelnytska et al [19], Lukashevich and Semigina [23], Ovod [32], Trubavina [49]; professional training of social workers is investigated by Omelchenko et al [30], Pinaeva and O. [35], Povidaychyk [36], Savelchuk and Bybyk [39], Slozanskaya and Horishna [45].…”
Section: Introductionmentioning
confidence: 99%